Pulmonary Hypertension Secondary to Myxomatous Mitral Valve Disease in Dogs: Current Insights into the Histological Manifestation and Its Determining Factors - Arkadiusz Grzeczka; Urszula Pasławska; Szymon Graczyk; Paulina Antosik; Marcin Zawadzki; Robert Pasławski (Applied Sciences, 2024)
Pulmonary venous hypertension (PVH) is caused by deteriorating left ventricular function. The most common cause of PVH in dogs is myxomatous mitral valve degeneration (MMVD). It causes left ventricular volume overload and an increase in left atrial and pulmonary venous pressure (PVH), which leads to pulmonary vascular wall remodeling and contributes to the perpetuation and worsening of PVH. Pulmonary vascular wall remodeling is also characteristic of pulmonary arterial hypertension (PAH). However, the changes in PVH arise secondary to heart failure and vascular remodeling progresses as the disease progresses. On the other hand, PAH is a primary disease that can be triggered, for example, by the use of certain drugs. Similar structural changes may suggest the influence of similar pathophysiological mechanisms or the intermediation of similar mediators. Therefore, this article discusses recent and hitherto uncommented findings elucidating the pathophysiology of the processes and influences on the pattern of histological changes observed in pulmonary hypertension secondary to degenerative mitral valve disease. In particular, we focus on the activity of factors such as endothelin, serotonin, and nitric oxide, which are involved in pulmonary vascular wall remodeling in both PVH and PAH.